Analisis Ekonomis Dan Efektivitas Anggaran Pendapatan (PNBP) Dan Belanja Pada Kantor Pertanahan Kabupaten Lampung Selatan - Sari, Pipit Novila; Alie, Maria Septijantini; Indriyani, Susi (Akuisisi : Jurnal Akuntansi, 2024)
The objective of this study was to understand the economical and effective implementation of the State Revenue and Expenditure Budget at the government institution. Data sources used in this study are Budget Realization Report the period of 2022 was obtained from the Kantor Pertanahan Kabupaten Lampung Selatan. This research uses economic analysis and effectiveness analysis. The results of the research shown by the percentage of budget realization was less than 100% (<100%). The results of the research show that Economic level in 2022 fiscal yearutilization felt into the economical category as shown by the percentage of budget realization was less than 100% (<100%). The effective level of achievement for non-tax state income realization 2022 fiscal year felt into a sufficient effective criteria with the effective ratio was 150%; while that for the expenditure felt into a sufficient ineffective criteria with an average effective ratio was 37,4%. This economical and effective implementation of State Revenue and Expenditure Budget must continue to be impoved.